MANAJEMEN PEMBERDAYAAN MASYARAKAT SEBAGAI USAHA KONSERVASI DANAU RAWA PENING DESA KEBONDOWO KECAMATAN BANYUBIRU KABUPATEN SEMARANG - Windra Hariyani; Hesti Lestari; Dewi Rostyaningsih (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2023)
This study aims to (1) identify and analyze community empowerment management as a conservation effort for Rawa Pening Lake in Kebondowo Village and (2) identify and analyze the driving and inhibiting factors in community empowerment as a conservation effort for Rawa Pening Lake in Kebondowo Village. In this study using qualitative methods with research subjects consisting of the Head of Kebondowo Village, the community in Kebondowo Village, the Semarang Regency Environmental Service, and the Semarang Regency Community and Village Empowerment Service. Data collection in this study was carried out by means of observation, documentation, and interviews. The techniques used in analyzing the data are data reduction, data presentation, and drawing conclusions. The results of the study show: (1) community empowerment management as a conservation effort for Rawa Pening Lake is described through the functions of planning, organizing, directing, motivating, and controlling or supervising. In community empowerment as a conservation effort, Rawa Pening Lake has carried out these functions, but is still not perfect. In the planning function, there is still an unclear vision and mission, as well as standards that have not been set. The organizing function, facilities and infrastructure in supporting community empowerment activities are still not as needed. In the directive function, it has not been able to change the behavior of the entire Kebondowo Village community, due to the different quality of human resources so that community acceptance is different. The motivational function has been carried out well, where the community has responsibility, discipline, and enthusiasm. In control and supervision, the results and impact assessments have not used the standards set at the planning stage. The supporting factors consist of village potential, the presence of environmental cadres, and community enthusiasm, while the inhibiting factors consist of budget, human resources, there is no collaboration between agencies, and internal and external communication.